Horizontal Cleavage Meniscus Tear Repaired Using a Cerclage Technique - Ian S. MacLean MD; David R. Diduch MD (SAGE Publishing, 2022)
Background: Horizontal meniscal cleavage tears often occur in older individuals and have a degenerative component. Commonly, these are managed with partial meniscectomy. However, this results in significantly decreased contact area and increased peek contact forces. Arthroscopic repair has shown comparable results with repairs of other tear types. Indications: Cerclage repair is performed for a horizontal cleavage tear in individuals without significant arthritis and in whom partial meniscectomy would remove an unacceptably large portion of meniscal tissue. Technique Description: Using standard arthroscopy portals, a self-retrieving suture passing device is used to pass a #0 high-strength suture through the periphery of the meniscus. Arthroscopic knots are tied on the superior surface of the meniscus and pushed as far posteriorly as possible. A small 1-cm incision is made just through skin on the proximal, posteromedial border of the tibia. Through this a spinal needle is placed percutaneously to pass a Chia into the joint just posterior to the knot. A curved spinal needle from an outside-in meniscal repair kit may be used as this provides a better trajectory to tears closer to the root attachment. The Chia and suture limbs are retrieved out the front of the knee, and then the suture tails are shuttled out the back of the knee. This is repeated until the repair is complete. The suture limbs are then cut below skin. Results: After arthroscopic all-inside repair of horizontal cleavage tears, patients do well. Outcomes are similar to repairs of other meniscal tear types. In all, 80% of patients are satisfied with their results, and there is an 11% to 12% failure rate which is comparable to other types of tear repairs. Discussion: All-inside cerclage repair should be considered for individuals sustaining a horizontal cleavage tear. This preserves meniscal tissue compared to partial meniscectomy and yields good healing rates and outcomes. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.